Amorphous Ge-Bi-Se Thin Films: A Mass Spectrometric Study - Mawale, Ravi; Mandal, Govinda; Bouška, Marek; Gutwirth, Jan; Bora, Pankaj Lochan; Nazabal, Virginie; Havel, Josef; Němec, Petr (Scientific reports, 2019)
The Ge-Bi-Se thin films of varied compositions (Ge content 0-32.1 at. %, Bi content 0-45.7 at. %, Se content 54.3-67.9 at. %) have been prepared by rf magnetron (co)-sputtering technique. The present study was undertaken in order to investigate the clusters generated during the interaction of laser pulses with Ge-Bi-Se thin films using laser ablation time-of-flight mass spectrometry. The stoichiometry of the clusters was determined in order to understand the individual species present in the plasma plume. Laser ablation of Ge-Bi-Se thin films accompanied by ionization produces about 20 positively and/or negatively charged unary, binary and ternary (Gex+, Biy+, Sez+/-, GexSez+/-, BiySez+/- and GexBiySez-) clusters. Furthermore, we performed the laser ablation experiments of Ge:Bi:Se elemental mixtures and the results were compared with laser ablation time-of-flight mass spectrometry analysis of thin films. Moreover, to understand the geometry of the generated clusters, we calculated structures of some selected binary and ternary clusters using density functional theory. The generated clusters and their calculated possible geometries can give important structural information, as well as help to understand the processes present in the plasma processes exploited for thin films deposition.